Accelerated gap collapse in a Slater antiferromagnet - Picano, Antonio; Eckstein, Martin (Physical Review B, 2021)
We study the melting of long-range antiferromagnetic order in the Hubbard model after an interaction quench, using nonequilibrium dynamical mean-field theory. From previous studies, the system is known to quickly relax into a prethermal symmetry-broken state. Using a convergent truncation of the memory integrals in the Kadanoff Baym equations, we unravel the subsequent relaxation dynamics of this state over several orders of magnitude in time. At long times, the prethermal state can be characterized by a single slow variable, which is related to the conduction band population. The dynamics of this variable is highly nonlinear, with a pronounced speedup once the gap falls below a certain value. This behavior indicates that nonthermal order can be self-sustained on some timescale because of a thermalization bottleneck is provided by the gap opened by the long-range order itself. These results cannot be reproduced using simple Fermi's golden rule estimate for the evolution of the conduction band population, and are distinct from the conventional scenario for the relaxation of prethermal states, in which a slow thermalization follows a rapid prethermalization.
CRIS-Team Scopus Importer:2021-04-30

Inhomogeneous disordering at a photoinduced charge density wave transition - Picano, Antonio; Grandi, Francesco; Eckstein, Martin (Physical Review B, 2023)
Using ultrashort laser pulses, it has become possible to probe the dynamics of long-range order in solids on microscopic timescales. In the conventional description of symmetry-broken phases within time-dependent Ginzburg-Landau theory, the order parameter evolves coherently, with small fluctuations along an average trajectory. Recent experiments, however, indicate that some systems can support a different scenario, named ultrafast inhomogeneous disordering, where the average order parameter is no longer representative of the state on the atomic scale. Here we theoretically show that ultrafast disordering can occur in a minimal, yet paradigmatic, model for a Peierls instability if atomic scale inhomogeneities of both the electronic structure and the charge density wave order parameter are taken into account. The latter is achieved using a nonequilibrium generalization of statistical dynamical mean-field theory coupled to stochastic differential equations for the order parameter.
CRIS-Team Scopus Importer:2023-06-30

Memory truncated Kadanoff-Baym equations - Stahl, Christopher; Dasari, Nagamalleswara Rao; Li, Jiajun; Picano, Antonio; Werner, Philipp; Eckstein, Martin (Physical Review B, 2022)
The Keldysh formalism for nonequilibrium Green's functions is a powerful theoretical framework for the description of the electronic structure, spectroscopy, and dynamics of strongly correlated systems. However, the underlying Kadanoff-Baym equations (KBE) for the two-time Keldysh Green's functions involve a memory kernel, which results in a high computational cost for long simulation times tmax, with a cubic scaling of the computation time with tmax. Truncation of the memory kernel can reduce the computational cost to linear scaling with tmax, but the required memory times will depend on the model and the diagrammatic approximation to the self-energy. We explain how a truncation of the memory kernel can be incorporated into the time-propagation algorithm to solve the KBE, and investigate the systematic truncation of the memory kernel for the Hubbard model in different parameter regimes, and for different diagrammatic approximations. The truncation is easier to control within dynamical mean-field solutions, where it is applied to a momentum-independent self-energy. Here, simulation times up to two orders of magnitude longer are accessible both in the weak and strong coupling regime, allowing for a study of long-time phenomena such as the crossover between prethermalization and thermalization dynamics.
CRIS-Team Scopus Importer:2022-04-22

Quantum Boltzmann equation for strongly correlated electrons - Picano, Antonio; Li, Jiajun; Eckstein, Martin (Physical Review B, 2021)
Collective orders and photoinduced phase transitions in quantum matter can evolve on timescales which are orders of magnitude slower than the femtosecond processes related to electronic motion in the solid. Quantum Boltzmann equations can potentially resolve this separation of timescales, but are often constructed by assuming the existence of quasiparticles. Here we derive a quantum Boltzmann equation which only assumes a separation of timescales (taken into account through the gradient approximation for convolutions in time), but is based on a nonperturbative scattering integral, and makes no assumption on the spectral function such as the quasiparticle approximation. In particular, a scattering integral corresponding to nonequilibrium dynamical mean-field theory is evaluated in terms of an Anderson impurity model in a nonequilibrium steady state with prescribed distribution functions. This opens the possibility to investigate dynamical processes in correlated solids with quantum impurity solvers designed for the study of nonequilibrium steady states.
CRIS-Team Scopus Importer:2021-08-20

Stochastic semiclassical theory for nonequilibrium electron-phonon coupled systems - Picano, Antonio; Grandi, Francesco; Werner, Philipp; Eckstein, Martin (Physical Review B, 2023)
We discuss a semiclassical approach to solve the quantum impurity model within nonequilibrium dynamical mean-field theory for electron-lattice models. The effect of electronic fluctuations on the phonon is kept beyond Ehrenfest dynamics, leading to a stochastic phonon evolution with damping and noise terms that are self-consistently determined by the electronic correlation functions in the fluctuating phonon field. Together with a solution of the electronic model based on a nonperturbative quantum Boltzmann equation, the approach can be used to address the coupled dynamics of the electrons and the lattice during photoinduced phase transitions. Results for the Anderson-Holstein model are benchmarked against numerically exact quantum Monte Carlo data. We find good agreement for the phonon distribution function at temperatures comparable to the charge ordering temperature. The general formulation can be extended to models with electron-electron interactions or multiorbital systems.
CRIS-Team Scopus Importer:2023-08-04